Clause structure and distribution changes: A translation analysis of adjective clauses in the kite runner - Dewi, Rika Erlin; Suparto (Communications in Humanities and Social Sciences, 2025)
This study analyzes the translation of English adjective clauses into Indonesian in The Kite Runner by Hosseini (2003) and its translation by Nugrahani (2008). Using Chesterman's (2000) translation strategies framework, this descriptive analytical study explores how syntactic, semantic, and pragmatic translation strategies are applied to adapt complex English grammatical structures to Indonesian. The study focuses on identifying the strategies employed—such as literal translation, transposition, unit-shift, synonymy, antonymy, and cultural adaptation—and evaluating their effectiveness in preserving the meaning of the source text while ensuring accuracy, readability, and fluency in the target text. The findings show that syntactic strategies, including literal translation and transposition, were commonly used to accommodate the structural differences between the two languages, while semantic and pragmatic strategies were employed to enhance readability and cultural relevance. The quality of the translation was assessed using Nida and Taber’s (1982) principles of dynamic equivalence, with high ratings in accuracy and readability. This study contributes to translation practice by offering insights into effective strategies for translating adjective clauses across languages with divergent grammatical rules and suggests directions for future research on clause translation in various genres.